Gambaran Pengetahuan dan Perilaku Pasien dan Keluarga Tentang Manajemen DM Tipe 2: Patient and Family Knowledge and Behavior About Type 2 DM Management - Berthiana T; Fetty Rahmawati; Noor Saleha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Diabetes mellitus is a chronic disease caused by heredity and/or lack of insulin production by the pancreas, or due to ineffective insulin function thereby increasing the concentration of glucose in the blood, which ultimately damages various body systems, especially blood vessels and nerves. Worldwide there are approximately 224 million cases of diabetes with 1.5 million mortality rates and an estimated one in eleven people in the world has diabetes. The four pillars of DM management which discuss DM education, DM diet, DM physical exercise and DM treatment. To find out the knowledge and behavior of patients and families about type 2 DM management. In this study, secondary data was used by analyzing previous journals and journal searches using the Google search engine. Scholar It is known based on three journals the results of patient and family knowledge levels about DM management, regarding DM education in the good category with results (73.3%) patient knowledge about diet is in the good category with results (83.8%), while knowledge about physical exercise get good category results (77.5%) and less knowledge (60.0%) and less knowledge about drugs. (61.3%) and good knowledge (90.0%). Behavioral adherence to education, diet, physical activity, adherence to taking medication in type 2 DM patients is still a lot of disobedience. Knowledge and behavior of patients and families have in common in discussing the four pillars of DM management which discuss DM education, DM diet, DM physical exercise and DM treatment.